A model for describing the light response of the nonphotochemical quenching of chlorophyll fluorescence - Serôdio, João (2018)
The operation of photosynthetic energy-dissipating processes is commonly characterized by measuring the light response of the nonphotochemical quenching (NPQ) of chlorophyll ﬂuorescence, or NPQ versus E curves. This study proposes a mathematical model for the quantitative description of the generic NPQ versus E curve. The model is an adaptation of the Hill equation and is based on the close dependence of NPQ on the xanthophyll cycle (XC). The model was tested on NPQ versus E curves measured in the plant Arabidopsis thaliana and the diatom Nitzschia palea, representing the two main types of XC, the violaxanthin–antheraxanthin–zeaxanthin (VAZ) type and the diadinoxanthin–diatoxanthin (DD–DT) type, respectively. The model was also ﬁtted to a large number of published light curves, covering the widest possible range of XC types, taxa, growth conditions, and experimental protocol of curve generation. The model provided a very good ﬁt to experimental and published data, coping with the large variability in curve characteristics. The model was further used to quantitatively compare the light responses of NPQ and of PSII electron transport rate, ETR, through the use of indices combining parameters of the models describing the two types of light–response curves. Their application to experimental and published data showed a systematic large delay of the buildup of NPQ relatively to the saturation of photochemistry. It was found that when ETR reaches saturation, NPQ is on average still below one ﬁfth of its maximum attainable level, which is only reached at irradiances about three times higher. It was also found that organisms having the DD–DT type of XC appeared to be able to start operating the XC at lower irradiances than those of the VAZ type.